1994
DOI: 10.1097/00001888-199407000-00014
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of the costs of administration of an OSCE (objective structured clinical examination)

Abstract: The OSCE was more time-consuming and more expensive in human and material costs than the SO examination. However, costs of the OSCE can be substantially reduced from approximately U.S. $35 to U.S. ! per student per station if test developers, standardized patients, support staff, and examiners can donate their time. The authors compare the costs and time requirements of their OSCE with those of other OSCEs reported in the literature, and they provide guidelines to assist educators in deciding whether the costs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 0 publications
1
52
0
2
Order By: Relevance
“…The OSCE has been integrated into undergraduate medical education 3 and can help screen surgical potential at an early stage, which has obvious safety and financial implications. 4 Recently, surgical educators have discussed the importance of identifying appropriate individual differences in aptitude and personality that can also be used to determine surgical potential. 5 Notably, Arora and colleagues 6,7 have encouraged research on personality differences in responding to stress; a factor that surgeons 8 and surgical trainees (e.g., OSCE) 9,10,11 alike, encounter on a regular basis.…”
Section: Introductionmentioning
confidence: 99%
“…The OSCE has been integrated into undergraduate medical education 3 and can help screen surgical potential at an early stage, which has obvious safety and financial implications. 4 Recently, surgical educators have discussed the importance of identifying appropriate individual differences in aptitude and personality that can also be used to determine surgical potential. 5 Notably, Arora and colleagues 6,7 have encouraged research on personality differences in responding to stress; a factor that surgeons 8 and surgical trainees (e.g., OSCE) 9,10,11 alike, encounter on a regular basis.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Experiences in other health professions have established the reliability and validity of a well-constructed and implemented OSCE. [8][9][10] The use of OSCEs in high-stakes settings (such as certification examinations and maintenance of competency reviews) has demonstrated their value in assessing clinical competency. For example, the Medical Council of Canada has used an OSCE in its entry-topractice examinations since 1994.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Since the 1970s, the College of Pharmacists of British Columbia (CPBC, the regulatory body for pharmacy practice in Canada's third largest province, responsible for licensing of pharmacists) began using standardized practice problems and patient simulations in an OSCE format as a method of evaluating entry-to-practice and continuing competency of its pharmacist members. 11 In 1996, the Ontario College of Pharmacists (the regulatory/licensing body for pharmacy practice in Canada's largest province) instituted an OSCE as part of its compulsory Quality Assurance and Practice Review program for all practicing pharmacists in Canada's largest province.…”
Section: Introductionmentioning
confidence: 99%
“…18 Also, scant data exists regarding total manpower hours required to develop and administer OSCEs, although Cusimano and colleagues approximated that 8.2 person-hours per student were required to develop and implement a 6-station OSCE (1.4 hours per student per station). 19 Perhaps partly due to these financial and time constraints, many US colleges and schools of pharmacy have developed OSCEs with a low number of stations, use individuals instead of groups to write cases, use nonprofessional standardized patients, and have limited ability to ensure consistency of the patient's role portrayal either due to limited training and/or lack of space and technology that allows viewing of encounters. In such cases, it is questionable whether or not an OSCE as defined by Harden 1 is being administered.…”
Section: Discussionmentioning
confidence: 99%